2018
DOI: 10.7717/peerj.6093
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gelsemine on oxidative stress and DNA damage responses of Tetrahymena thermophila

Abstract: Gelsemine is an important toxic substance extracted from Gelsemium elegans, which has a lot of biological functions in cells and organisms, but its toxicity has been rarely reported in Tetrahymena thermophila. In this study, we used the protozoan T. thermophila as an experimental model to investigate the potential toxicity-induced mechanism of gelsemine in the unicellular eukaryote. Our results clearly showed gelsemine inhibited T. thermophila growth in a dose-dependent manner. This exposure also resulted in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…MPK1 and MPK3 are critical components of MAP kinase signaling and their expressions were related to oxidative stress [28, 29]. Studies have shown that oxidative stress may be regulated by MAPK pathway [55, 56, 57]. In our study, MPK1 and MPK3 increased significantly at 0.8 mg/mL koumine and suggested that koumine may involve oxidative stress through the MAPK pathway.…”
Section: Discussionsupporting
confidence: 61%
“…MPK1 and MPK3 are critical components of MAP kinase signaling and their expressions were related to oxidative stress [28, 29]. Studies have shown that oxidative stress may be regulated by MAPK pathway [55, 56, 57]. In our study, MPK1 and MPK3 increased significantly at 0.8 mg/mL koumine and suggested that koumine may involve oxidative stress through the MAPK pathway.…”
Section: Discussionsupporting
confidence: 61%
“…The first total syntheses of (±)-gelsemine were disclosed in 1994 by the groups of Johnson. Gelsemine and koumine of G. elegans inhibited Tetrahymena thermophila cells’ growth in a dose-dependent manner [14,15]. In the present study, two optical isomers, +/− gelsemine (1, 2), together with one known compound, koumine, were isolated from the whole plant of G. elegans (Figure 1).…”
Section: Introductionmentioning
confidence: 59%